2005
DOI: 10.1163/1568540054020523
|View full text |Cite
|
Sign up to set email alerts
|

Growth, energy allocation, and biochemical composition of the body of Chinese shrimp, Fenneropenaeus chinensis, fed different diets

Abstract: Five diets, i.e., fish flesh (FF), shrimp flesh (SF), clam foot (CF), polychaete worm (PW), a formulated diet (FD), and a mixture of the preceding five diets (MD), were fed to Chinese shrimp, Fenneropenaeus chinensis (initial weight 1.53 ± 0.05 g) for 30 days to investigate the effects of different diets on the energy allocation and body composition of Chinese shrimp. It was found that the model of allocation of ingested energy changed according to diet, and significant differences existed among treatments. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It has been reported that protein, ash, lipid and moisture contents of shrimp change according to nutrition, living area, size, catching season, seasonal and sexual variations as well as environmental conditions (Wen et al, 2001;Gökoğlu and Yerlikaya, 2003;Rosa and Nunes, 2004;Huang et al, 2005;Yerlikaya and Gökoğlu, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that protein, ash, lipid and moisture contents of shrimp change according to nutrition, living area, size, catching season, seasonal and sexual variations as well as environmental conditions (Wen et al, 2001;Gökoğlu and Yerlikaya, 2003;Rosa and Nunes, 2004;Huang et al, 2005;Yerlikaya and Gökoğlu, 2005).…”
Section: Resultsmentioning
confidence: 99%